PENERAPAN PENDEKATAN MATEMATIKA REALISTIK INDONESIA(PMRI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 3 LUBUKLINGGAU - Hurin Nabillah; Rani Refianti; Maria Luthfiana (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to determine the mathematics learning outcomes of students class VII SMP Negen 3 Lubuklinggau after using the application of the Indonesian Realistic Mathematics Education (PMRI) approach. The approach used in this research is a quantitative approach with a quasi-experimental research type. Negen 3 Lubuklinggau for the 2022/2023 academic year. The samples taken were class VII 4 with a total of 30 students. The data collection technique in the uu yahu research was a test technique, namely by giving students four questions. The results of this study showed that student learning outcomes experienced completeness of 86% with an average MLA of 71.92. Based on research using a t-test with a significant level = 0.05 with the results of the hypotensive test analysis showing the final ability of students with thong (2.434) > table (1.699), it can be concluded that students' learning outcomes in mathematics class VII SMP Negeri 3 Lubuklinggau for the 2022/2023 academic year after the application of the Indonesian realistic education approach (PMRI) to learning mathematics results.